Inovasi Pembelajaran: Strategi Kepala Sekolah Dalam Pengembangan Sarana dan Prasarana - maria_leli83, maria_leli83; Lilianti; Mujiati (Universitas Muhammadiyah Surabaya, 2024)
This study aims to analyze principals' strategies in developing facilities and infrastructure to support learning innovation. A qualitative case study approach was employed, involving in-depth interviews with principals, teachers, and administrative staff, as well as observations and document analysis. Results indicate that successful principals in learning innovation focus on integrating technology, such as educational software and interactive whiteboards, and developing flexible learning spaces. Collaborative approaches involving teachers, students, and the community proved effective. The conclusion is that principals' strategies significantly enhance educational quality through proactive and visionary management of facilities and infrastructure. The novelty of this research lies in emphasizing collaboration and professional training for principals, as well as the importance of sustainability in educational facility innovation.